New Ways of Analysing the History of Varieties of English – An Acoustic Analysis of Early Pop Music Recordings from Ghana - Schmidt, Sebastian (Research in Language, 2012)
Focusing on English in Ghana, this paper explores some ways in which early popular music recordings might be used to reconstruct the phonology of colonial and post-colonial Englishes in a situation where other recordings are (mostly) absent. While the history of standard and, to a certain degree, non-standard varieties of “Inner Circle Englishes” (Kachru 1986) has received linguistic attention, diachronic investigations of Outer Circle varieties are still the exception. For the most part, descriptions of the history of post-colonial Englishes are restricted to sociohistorical outlines from a macro-sociolinguistic perspective with little if any reference to the linguistic structure of earlier stages of the varieties. One main reason for this lack of diachronic studies is the limited availability of authentic historical data. In contrast to spoken material, written sources are more readily available, since early travel accounts, diaries or memoirs of missionaries, traders and administrators often contain quotes and at times there are even documents produced by speakers of colonial Englishes themselves (cf. the diary of Antera Duke, a late 18th century Nigerian slave trader; Behrendt et al. 2010). Such material provides insights into the morphology, syntax and the lexicon of earlier stages of varieties of English (cf. Hickey 2010), but it is inadequate for the reconstruction of phonological systems. Obtaining spoken material, which permits phonological investigation, is far more difficult, since there are comparatively few early recordings of Outer Circle Englishes. In such cases, popular music recordings can fill the gap. I will present first results of an acoustic analysis of Ghanaian “Highlife” songs from the 1950s to 1960s. My results show that vowel subsystems in the 1950s and 1960s show a different kind of variation than in present-day Ghanaian English. Particularly the STRUT lexical set is realized as /a, ɔ/ in the Highlife-corpus. Today, it is realized with three different vowels in Ghanaian English, /a, ε, ɔ/ (Huber 2004: 849). A particular emphasis will also be on the way Praat (Boersma and Weenink 2011) can be used to analyze music recordings.